2001
DOI: 10.1172/jci200112348
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-induced cortical actin remodeling promotes GLUT4 insertion at muscle cell membrane ruffles

Abstract: Insulin stimulates glucose uptake by recruiting glucose transporter 4 (GLUT4) from an intracellular compartment to the cell surface; this phenomenon is defective in type 2 diabetes. Here we examine the involvement of actin filaments in GLUT4 translocation and their possible defects in insulin resistance, using L6 myotubes expressing myc-tagged GLUT4. Insulin caused membrane ruffling, a dynamic distortion of the myotube dorsal surface. Fluorescence microscopy and immunogold staining of surface GLUT4myc coupled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
166
2
3

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(179 citation statements)
references
References 50 publications
8
166
2
3
Order By: Relevance
“…These results are consistent with recent studies reporting that high glucose treatment alone did not impair insulin-induced glucose uptake in adipocytes and skeletal muscle (Nelson et al, 2000;Kawanaka et al, 2001). However, an experimental condition of high glucose (25 mM) plus high insulin (100 nM) for 24 h exposure, demonstrated to produce insulin resistance in L6 myoblasts and 3T3-L1 adipocytes (Thomson et al, 1997;Tong et al, 2001), significantly decreased the insulinstimulated glucose uptake in H9c2 cells (Figure 2). It has been shown that insulin promotes membrane ruffling by a rapid remodeling of actin filaments and that the disruption of the actin cytoskeleton inhibited insulin-mediated GLUT4 translocation in myoblasts, fibroblasts and adipocytes (Tsakiridis et al, 1994;Clodi et al, 1998;Wang et al, 1998;Olson et al, 2001;Tong et al, 2001).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…These results are consistent with recent studies reporting that high glucose treatment alone did not impair insulin-induced glucose uptake in adipocytes and skeletal muscle (Nelson et al, 2000;Kawanaka et al, 2001). However, an experimental condition of high glucose (25 mM) plus high insulin (100 nM) for 24 h exposure, demonstrated to produce insulin resistance in L6 myoblasts and 3T3-L1 adipocytes (Thomson et al, 1997;Tong et al, 2001), significantly decreased the insulinstimulated glucose uptake in H9c2 cells (Figure 2). It has been shown that insulin promotes membrane ruffling by a rapid remodeling of actin filaments and that the disruption of the actin cytoskeleton inhibited insulin-mediated GLUT4 translocation in myoblasts, fibroblasts and adipocytes (Tsakiridis et al, 1994;Clodi et al, 1998;Wang et al, 1998;Olson et al, 2001;Tong et al, 2001).…”
Section: Discussionsupporting
confidence: 92%
“…To test an experimental hyperglycemic condition, cells were incubated in DMEM containing 25 mM glucose supplemented with 10% FBS, penicillin (100 U/ml) and streptomycin (100 µg/ml) for 0.5 or 24 h. Cells were serum starved for 24 h in DMEM containing 5 mM (control) or 25 mM (hyperglycemic condition) glucose, supplemented with 0.5% bovine serum albumin (BSA) (Fraction V; Sigma) and then compared to each other by incubating with or without 100 nM insulin (Porcine, Sigma I0259) for 10 min. To investigate an experimental condition of insulin resistance, cells were incubated for 24 h in DMEM supplemented with 10% FBS containing 5 mM glucose (control) or 25 mM glucose plus 100 nM insulin (insulin resistance condition) (Thomson et al, 1997;Tong et al, 2001) prior to serum starvation for 4 h in DMEM supplemented with 0.5% BSA, and treated with or without 100 nM insulin for 5-15 min.…”
Section: Aterials and M Ethods C Ell Culturementioning
confidence: 99%
See 2 more Smart Citations
“…If the membrane protein structure changes by extracellular forces such as peroxidation and glycosylation, its folding property will alter, thereby its lipid composition may have to change to match. Abnormal glucose transporters [41], decreased insulin receptor binding protein [42], Ca ++ transmembrane movement [43], alteration of uncoupling and remodelling of actin [44,45] are examples of altered membrane protein function depressed in diabetes and obesity. The red cell membrane is essentially an example of plasma membrane.…”
Section: Discussionmentioning
confidence: 99%